Evaluation of Acetylcholine Esterase and Protease Inhibitory Activity of Scopolamine Extracted from Datura innoxia - Shahwar, Durre; Asam Raza, Muhammad; Khan, Tania (Asian Journal of Chemistry, 2010)
Scopolamine was extracted from aerial parts of Datura innoxia and its structure was confirmed by spectroscopic analysis. Acetylcholine esterase and protease inhibitory activity was determined. The results indicated that this compound has significant acetylcholine esterase potential (69.5 ± 0.5 % inhibition, IC50 = 0.205 ± 0.009 mM), while moderate protease inhibition activity (31.7 ± 0.8 % inhibition).